Designing a Copper‐ and Silver‐Sulfide Composite with Co3O4 for High‐Performance Electrochemical Supercapacitors. Issue 2 (30th October 2018) - Pawar, Sachin A.; Patil, Dipali S.; Shin, Jae Cheol
Abstract: Electronic devices have driven modern lifestyle demands for efficient and environmentally friendly energy storage appliances. This paper reports the simple design of an efficient, cost‐effective pseudocapacitor electrode based on copper sulfide (Cu2 S) and silver sulfide (Ag2 S) composites with cobalt oxide (Co3 O4 ) for high‐performance energy storage devices. A simple one‐pot approach was used to synthesize hexagonal sheets of Co3 O4 and a successive ionic layer adsorption and reaction method was exploited to coat these sheets with nanostructures of Cu2 S and Ag2 S. The resulting three‐dimensional (3D) Co3 O4 /Cu2 S and Co3 O4 /Ag2 S composite electrode contained a high loading of Cu2 S and Ag2 S nanoparticles (metal sulfides) on the hexagonal sheets of Co3 O4 (metal oxide), which offers a highly conductive network assisting in rapid charge‐transfer reactions and reduces the internal resistance of the electrode. A symmetrical supercapacitor based on Co3 O4 /Cu2 S//Co3 O4 /Cu2 S showed a high areal capacitance of 1080 mF cm −2, which was significantly higher than that of the Co3 O4 /Ag2 S//Co3 O4 /Ag2 S symmetric supercapacitor (645 mF cm −2 ). These results show that the Co3 O4 /Cu2 S composite heterostructure is a promising electrode architecture for high performance pseudocapacitors. Abstract : Putting on a performance: The composites of metal oxide/metal sulfides are synthesized by using hydrothermal and successive ionic layer adsorption and reaction (SILAR) techniques for superior supercapacitors.